Avaliação da qualidade de inserção urbana do empreendimento Vila Penha do Rio do Peixe, em Itapira (SP) - Araújo, Jefferson Cruz (Universidade Federal de São Carlos, 2022)
This work analyzed the quality of urban insertion of the Vila Penha do Rio do Peixe, a housing complex of social interest (HIS), located in Itapira (SP). As a basis for the formulation of criteria and parameters of analysis, two evaluation instruments were considered: 1) "Urban Insertion Assessment Tool for The Enterprises of Track 1 of the My House My Life Program", the ITDP - Institute of Transport and Development Policies, and LabCidade (FAUUSP) - Laboratory Public Space and Law to the City of the Faculty of Architecture and Urbanism of USP. 2) "Casa Azul Seal: Good practices for more sustainable housing", an instrument of socio-environmental classification of CEF - Caixa Econômica Federal. In terms of Bibliographic Review, two-axis compilations were made that served as the basis for the desired analyses. The first, in relation to the more general themes involving different urban conditions such as land use, mobility and infrastructure provision. The second axis, focusing on the case study, through the survey and study of current legal documents, as well as cartoriais documents, projects and descriptive memorials. From this repertoire, an analysis of the transformation process and the urban conditions of Vila Penha do Rio do Peixe was performed, using criteria and parameters formulated based on the two pre-selected evaluation instruments. The results obtained point to a condition in which trade, service provision and public equipment of daily and eventual use, are being sufficiently well served. In the sporadic item, the supply was insufficient, considering the weaknesses observed in the analysis of the services provided by public transport, such as low frequency and restrictions resulting from the period of care. Regarding the impacts, some generating poles (Frigorific and Industry) were identified, but with intermittent and localized effects. It is expected, therefore, that this research can contribute to a better understanding and improvement of the processes of analysis of the urban conditions and urban sectors and bring subsidies for overcoming the weaknesses identified in Vila Penha do Rio do Peixe.
Quality assessment of urban insertion of the Vila Penha do Rio do Peixe enterprise, in Itapira (SP)
Evaluación de la calidad de la inserción urbana de la Vila Penha do Rio do Peixe, em Itapira (SP)
Keywords: Inserção urbana; Uso do solo urbano; infraestrutura urbana; Mobilidade urbana; Itapira (SP); Urban insertion; Land use; Urban infrastructure; Urban mobility; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::FUNDAMENTOS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::INFRA-ESTRUTURAS URBANAS E REGIONAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::LEGISLACAO URBANA E REGIONAL